2014
DOI: 10.1007/s00441-014-2067-6
|View full text |Cite
|
Sign up to set email alerts
|

Arrested development of the dorsal column following neonatal spinal cord injury in the opossum, Monodelphis domestica

Abstract: Developmental studies of spinal cord injury in which regrowth of axons occurs across the site of transection rarely distinguish between the recovery of motor-controlling pathways and that of ascending axons carrying sensory information. We describe the morphological changes that occur in the dorsal column (DC) of the grey short-tailed opossum, Monodelphis domestica, following spinal cord injury at two early developmental ages. The spinal cords of opossums that had had their mid-thoracic spinal cords completely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This approach successfully identified broad statistically significant decreases in the expression of neural progenitor and neural stem cell–related genes and increases in expression of markers of spinal cord maturation (myelination, mature neurons and glia) during development (Figure 6b). These gene changes are not surprising given that the cord is developing rapidly during this time resulting in approximately a fivefold increase in number of descending axons (Fry et al, 2003) and an approximate doubling in the cross‐sectional area of the spinal cord during this developmental period (Wheaton et al, 2015). These developmental findings are consistent with our chosen methodology being sufficiently robust and having the capacity to identify biologically relevant and important gene expression changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach successfully identified broad statistically significant decreases in the expression of neural progenitor and neural stem cell–related genes and increases in expression of markers of spinal cord maturation (myelination, mature neurons and glia) during development (Figure 6b). These gene changes are not surprising given that the cord is developing rapidly during this time resulting in approximately a fivefold increase in number of descending axons (Fry et al, 2003) and an approximate doubling in the cross‐sectional area of the spinal cord during this developmental period (Wheaton et al, 2015). These developmental findings are consistent with our chosen methodology being sufficiently robust and having the capacity to identify biologically relevant and important gene expression changes.…”
Section: Discussionmentioning
confidence: 99%
“…Cords were collected for RNA sequencing analysis +1, +3 or +7 days later, along with age‐matched control tissues. Detailed procedures for completely transecting the lower thoracic (T10) spinal cord in these pups have been described previously (Wheaton et al, 2011; Wheaton et al, 2013; Wheaton, Noor, Dziegielewska, Whish, & Saunders, 2015). Briefly, opossum pups were anesthetized to a surgical level using inhaled isoflurane (3% in O 2 ‐enriched air), either while still attached at the teat to the anesthetized mother (in the case of P7SCI pups) or individually (in the case of the more mature P28SCI pups).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have used the marsupial South American opossum ( Monodelphis domestica ) and North American opossum ( Didelphis virginiana ) to demonstrate the effects of spinal cord injuries at different stages of development ( Fry & Saunders, 2000; Martin & Xu, 1988; Saunders et al , 1989; Saunders et al , 1998; Wang et al , 1996; Wang et al , 1998 a ; Wheaton et al , 2011; Wheaton et al , 2013; Wheaton et al , 2015; Xu & Martin, 1992). It has been shown that when pups were injured early in development at post-natal day P7, regrowth of supraspinal neuronal axons across the lesion site was demonstrated (termed the “permissive” stage, as previously suggested for the period when functional repair occurred in chick embryonic spinal cord following SCI; Keirstead et al , 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Terman et al , 1999; Wang et al , 1998 a ). Several attempts have been made to identify cellular and molecular changes that could explain this shift in the ability of axons to bridge the site of injury ( Noor et al , 2011; Saunders et al , 1998; Saunders et al , 2014; Terman et al , 1999; Wang et al , 1998 b ; Wheaton et al , 2015) and some suggestions that it could be related to the onset of myelination were also put forward ( Bandtlow, 2003; Saunders et al , 2014; Wheaton et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“… 2014 ) or spinal cord injury treatment (Wheaton et al. 2015 ). Moreover, after sequencing its genome by Mikkelsen et al.…”
Section: Introductionmentioning
confidence: 99%